Digital Payments and their Role in Enhancing Financial Transactions Efficiency - Calderon, Allan A. (International Journal of Economics and Financial Issues, 2024)
The concept of digital payments is examined in relation to the improvement of the performance of financial transactions. The key research objectives include; The evaluation of speed in transactions that have been enhanced, The reduction in cost of the transactions that is in relation to the current trend, The increase in frequency of the transactions that has been realized, The decrease in error rate in the use of the digital payment systems, and The general satisfaction of the users in engaging in the digital payment systems. In support, the research uses both quantitative data analysis of the sample of 47 businesses alongside qualitative case studies to get deeper understanding of the effects of digital payments. The quantitative findings reveal a 66 percent prevalence rate for the identified clinical manifestations of PTSD in the participants. 7% improvement in the transaction time, 50% cut in the transaction costs, 150% increase in frequency of transactions, 80% decline in the errors, and 40. This resulted to a 6% boost in the user satisfaction scores. These results show that there are great advantages when using digital payments in the aspect of speed and precision. The qualitative findings also support these outcomes and add basic utilitarian viewpoints originating from business owners and consumers. The study supports the theoretical framework of the Transaction Cost Theory and proves that digital payments minimize costs and increase operational effectiveness. The implications are far-reaching for the businesses and the financial institutions where it is recommended that they embrace digital payment systems to improve performance and competitiveness. As for the future research suggestions, it is recommended to focus on the samples’ increase and the inclusion of more diverse participants, the use of the longitudinal research designs, and the analysis of the effect of the modern technologies such as blockchain and artificial intelligence on the digital payments. The recommendations are more down-to-earth and stress the necessity of strategy, training, support, and secure IT solutions.